Essential Strategic Management Accounting Tools Used for Making Investment Decisions at Enterprises in EU - Pylypiv, Nadiya; Pіatnychuk Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
Slow current modernization reforms in the economic sector have significantly weakened the competitiveness of enterprises in EU; therefore, there is a great need for new tools in the managerial decision-making process. Information provision of the decision-making process on expediency of investment activity in the form of capital investments is formed within the limits of strategic management accounting. In the research except for various analytical methods (analysis, synthesis, comparison, grouping, etc.) a “decisions tree” method is used for choosing a reasonable solution. In the study, strategic management accounting has been defined as a separate kind of management accounting, which involves generation of high-quality information. Certain tools may be applied within it for the decisions made by managers, based on established business partnership with successful implementation of business strategy. Five most widespread groups of tools of strategic management accounting are cost accounting; planning, monitoring and evaluation of effectiveness; strategic decisions; competitor accounting; customer accounting. It is recommended to complete the list of instruments integrated within the five groups by a separate group – a specific category of supplier accounting that would contribute to the generation of more complete and qualitative information provision for the process of making managerial decisions on the appropriateness of capital investments in the investment activity of the enterprise in EU. The research made it possible to reach the following conclusions. Important components should be taken into account in order to fulfil strategic management accounting of the company in a proper way. Those are data sources choice, collecting and processing of information, choice of instruments of strategic management accounting, formation of internal regulation of strategic management accounting, development and supply of accounting and analytical information; process of solutions development, and the choice, which can provide generation of necessary information for competitive managerial decisions made by managers. Application of advanced tools for strategic management accounting, which give information to meet issues related to the characteristics of consumers, competitors, suppliers, project costs, assessment of investment feasibility in the project, is caused by the necessity of competitive decision-making with the help of the above-offered decisions tree tool usage